2021
DOI: 10.1111/ecc.13411
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s worry about cancer and the general practitioner’s suspicion of cancer or serious illness: A population‐based study in Denmark

Abstract: Although the literature is conflicting and the link between time and prognosis is complicated by, for example confounding by indication, recent studies suggest that the prognosis of cancer improves when the cancer is diagnosed in a timely manner (Neal et al., 2015;Rubin et al., 2015;Tørring et al., 2019). Thus, it is pivotal to continuously optimise cancer diagnostics and treatment. The majority of cancer patients initially consult their general practitioner (GP) with symptoms before diagnosis (Allgar and Neal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This study showed that patients with psychiatric disorders may be more likely to worry about cancer when presenting symptoms to their GP. Given that this population was diagnosed with cancer, patient worry can be regarded as positive, as it has been associated with the GP suspecting cancer [ 48 ]. Yet, if worry is present regardless of a subsequent cancer in patients with psychiatric disorders [ 46 , 47 ], the GP must balance between patient worry due to psychiatric distress and worry due to potential cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that patients with psychiatric disorders may be more likely to worry about cancer when presenting symptoms to their GP. Given that this population was diagnosed with cancer, patient worry can be regarded as positive, as it has been associated with the GP suspecting cancer [ 48 ]. Yet, if worry is present regardless of a subsequent cancer in patients with psychiatric disorders [ 46 , 47 ], the GP must balance between patient worry due to psychiatric distress and worry due to potential cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, if worry is present regardless of a subsequent cancer in patients with psychiatric disorders [ 46 , 47 ], the GP must balance between patient worry due to psychiatric distress and worry due to potential cancer symptoms. This may represent a diagnostic challenge in this patient group as the GP’s suspicion of cancer can be based on, for example, the patient’s worry [ 48 ].…”
Section: Discussionmentioning
confidence: 99%